(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article examines the development of children’s behavior and emotions as a psychological problem. Also, the place and role of fairy tales in the development of children’s behavior and emotions is highlighted.